Toward a naturalistic political theory : Aristotle, Hume, Dewey, evolutionary biology, and deep ecology - Hoy, Terry (Praeger, 2000)
This book seeks to establish the basis for a naturalistic political theory as a continuity from the philosophy of Aristotle through the contributions of Hume, Dewey, Evolutionary Biology and Deep Ecology.